2020
DOI: 10.1016/j.yjmcc.2020.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sympatho-vagal interaction on ventricular electrophysiology and their modulation during beta-blockade

Abstract: The effects of sympatho-vagal interaction on heart rate (HR) changes are characterized by vagal dominance resulting in accentuated antagonism. Complex autonomic modulation of ventricular electrophysiology may exert prognostic arrhythmic impact. We examined the effects of concurrent sympathetic (SNS) and vagus (VNS) nerve stimulation on ventricular fibrillation threshold (VFT) and standard restitution (RT) in an isolated rabbit heart preparation with intact dual autonomic innervation, with and without beta-bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In this study, electrophysiologic remodeling in HF was assessed using single autonomic nerve stimulation. We have previously characterized the effects of sympatho-vagal interaction on ventricular electrophysiology of normal hearts, demonstrating the lack of accentuated antagonism (and therefore prevailing sympathetic effect) at the ventricular level [ 10 ]. Instinctively, future studies should assess sympatho-vagal interaction in the in vitro HF model to mimic the complex sympatho-vagal interaction in real life HF population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, electrophysiologic remodeling in HF was assessed using single autonomic nerve stimulation. We have previously characterized the effects of sympatho-vagal interaction on ventricular electrophysiology of normal hearts, demonstrating the lack of accentuated antagonism (and therefore prevailing sympathetic effect) at the ventricular level [ 10 ]. Instinctively, future studies should assess sympatho-vagal interaction in the in vitro HF model to mimic the complex sympatho-vagal interaction in real life HF population.…”
Section: Discussionmentioning
confidence: 99%
“…The animal was sacrificed with an overdose of intravenous pentobarbitone sodium (60 mg) and heparin (500 U). Of note, pentobarbitone sodium was chosen due to its inert effect on autonomic function not only in rabbits but other animal models [ [8] , [9] , [10] ]. A 3F polypropylene catheter (Portex, Kent, UK) was inserted through the left ventricular apex for Thebesian venous effluent drainage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwartz et al [44] reported that in dogs with a healed anterior wall myocardial infarction, depressed barore ex sensitivity is a powerful indicator for risk strati cation not only after, but even before, the occurrence of a myocardial infarction. Chin et al [45] investigated the effects of sympathetic (SNS) and vagal stimulation (VNS) on VFT and standard restitution in an isolated rabbit heart preparation with and without beta-blockade. During concurrent high-frequency VNS, SNS prevailed in lowering VFT in a frequency-sensitive manner during low-or high-frequency stimulation, with accompanying steepening of relative restitution slope gradients.…”
Section: Autonomic Nerve and Vfmentioning
confidence: 99%
“…These agents exert anti-ischemic actions by reducing myocardial metabolic demand and by prolonging diastolic perfusion time secondary to their actions on the sinus node. Moreover, β-blockade obviates action potential changes and increases the threshold for ventricular fibrillation, counterbalancing the pro-fibrillatory effects of myocardial ischemia or sympathetic activation [ 19 ]. Based on these anti-ischemic and anti-arrhythmic properties, β-blockade has been consistently shown to lower SCD rates in post-MI patients.…”
Section: Antiarrhythmic Effects Of β-Blockadementioning
confidence: 99%